Nutritional Status and Dietary Pattern of Farm Women in Jodhpur District of Rajasthan - Kalash, Poonam; Kumawat, Subhita; Mishra, A K (Annals of Arid Zone, 2018)
The health of Indian women is intrinsically linked to their status in society and good health is essential for wellbeing of households. The present study was conducted in Jodhpur district of Rajasthan to study nutritional status and dietary pattern of the farm women during 2015-2017. The 41% farm women families own medium size land holdings and 75% families were nuclear. The 65% farm women have normal body mass index (BMI (18.5-25). The 55% farm women were having normal nutritional status whereas 16% and 19% were under weight and overweight, respectively. The finding of the study also showed that about 59% were between 31-50 years of age and majority (92%) were illiterate. Key words: Nutrition, diet pattern, farm women